Trajectory of rockfall on the uniform slope - Taijiang Chen; Guangcheng Zhang; Xin Xiang (地质科技通报, 2021)
Existing studies on the trajectory of the rockfall all regard the slope as a semi-infinite and uniform slope, but in actual working conditions, the slope is composed of heterogeneous materials.According to the different motion modes of rockfall, the slope surface is simplified to the structure of multi-layer rocks and soil materials.In the rolling stage, based on Hertz contact theory, the movement characteristics of falling rocks under different slope conditions are obtained, and the calculation formula for the tangential friction coefficient of the rockfall under the condition of the slope layering is given.In the collision phase, based on the law of conservation of energy, the normal recovery coefficient formula obtained by the quasi-static contact mechanics theory is used.The analytical solutions of the normal and tangential recovery coefficients of the rockfall under the condition of the arbitrary rock and soil material structure slope are derived, and then the motion parameters of the rockfall after the collision are obtained, According to the relationship between the speed of the rockfall and the amount of rebound after the collision, the judgment conditions for the transition of the motion mode of the rockfall after the collision are given.Finally, combined with the kinematics theorem, the motion trajectory of the falling rock under any layered slope condition in three motion modes is obtained. The theoretical formula is applied to the prediction of the motion trajectory of a rolling rock in a mountainous area, which verifies the applicability and validity of the theoretical formula.